2021
DOI: 10.1039/d0cp06127a
|View full text |Cite
|
Sign up to set email alerts
|

Pickup and reactions of molecules on clusters relevant for atmospheric and interstellar processes

Abstract: In this perspective, we review experiments with molecules picked up on clusters in molecular beams with the focus on the processes in atmospheric and interstellar chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 268 publications
(368 reference statements)
0
47
0
Order By: Relevance
“…The supersonic expansion + pickup principle has proved efficient for the production of mixed water clusters with dopant species and their subsequent characterization in the gas phase. 10 It has recently been applied to study alkali halides in water clusters 11 , 12 as well as anhydrous alkali halide clusters 12 15 with X-ray photoelectron spectroscopy (XPS). It was reported that the binding energies (BEs) of nanosolvated alkali and halide ions are insensitive to the counterions in water clusters with a few hundred water molecules, 11 similar to what has been observed in bulk solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The supersonic expansion + pickup principle has proved efficient for the production of mixed water clusters with dopant species and their subsequent characterization in the gas phase. 10 It has recently been applied to study alkali halides in water clusters 11 , 12 as well as anhydrous alkali halide clusters 12 15 with X-ray photoelectron spectroscopy (XPS). It was reported that the binding energies (BEs) of nanosolvated alkali and halide ions are insensitive to the counterions in water clusters with a few hundred water molecules, 11 similar to what has been observed in bulk solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the clusters enter a time-of-flight mass spectrometer (TOF), where the mass spectra after electron ionization are recorded. The experimental setup is described elsewhere, 23 , 24 and more details are given in the Supporting Information . We should mention that due to cluster fragmentation and the limited discrimination-free mass range of our TOF spectrometer, the mean cluster size has been derived from the Poisson distribution of the adsorbed molecular clusters rather than from the mass spectra, as detailed in the Supporting Information .…”
mentioning
confidence: 99%
“…Trends as well as dimensionless sphericity are comparable between both approaches. 4 ■ RESULTS AND DISCUSSION Implementation Overview. The development of the custom-built software that actively utilizes the power of GPU for higher precision simulation has posed multiple challenges.…”
Section: ■ Theoretical Overviewmentioning
confidence: 99%
“…These clusters are similar to atmospheric aerosol particles; therefore, their properties have a great meaning in the chemistry of atmosphere. 2 The cross section of water clusters can be estimated 3,4 by their capability to pick up other particles on their surface. After considering polarization and other phenomena which cause the pickup cross section to be larger than the geometric cross section, it has been deduced that there is still an unexplained increase for large clusters, which has been attributed to the clusters of irregular shape 4,5 rather than spherical.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation